2020
DOI: 10.1002/jcp.29905
|View full text |Cite
|
Sign up to set email alerts
|

Resistance mechanisms to immune checkpoints blockade by monoclonal antibody drugs in cancer immunotherapy: Focus on myeloma

Abstract: Multiple myeloma (MM) is a clonal B-cell malignancy characterized by the accumulation of neoplastic proliferation of a plasma cell in the bone marrow that produces a monoclonal immunoglobulin. The immune checkpoint inhibitors against programmed death-1/programmed death-1 ligand and cytotoxic T-lymphocyte an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 126 publications
(196 reference statements)
0
8
0
Order By: Relevance
“…[11][12][13] Cold tumors, such as prostate cancer and colon cancer, do not respond to single-agent ICB therapies because of their low immunogenicity. [13][14][15][16][17][18] Combination therapy has been used in the clinic to turn cold tumors into hot tumors in order to increase the efficacy of immunotherapy in recent years; such combination therapies include chemotherapy or radiation therapy combined with immunotherapy. 19 20 Chemotherapy and radiation can mainly lead to tumor cell apoptosis by disrupting cell division or destroying mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Cold tumors, such as prostate cancer and colon cancer, do not respond to single-agent ICB therapies because of their low immunogenicity. [13][14][15][16][17][18] Combination therapy has been used in the clinic to turn cold tumors into hot tumors in order to increase the efficacy of immunotherapy in recent years; such combination therapies include chemotherapy or radiation therapy combined with immunotherapy. 19 20 Chemotherapy and radiation can mainly lead to tumor cell apoptosis by disrupting cell division or destroying mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ORR has been increased by combined therapy independent of the PD-L1 level measured, not all patients benefit from the ICIs treatment, and this is termed a so-called primary resistance (30). Numerous studies have demonstrated the mechanisms of primary resistance in ICIs treatment (31)(32)(33), which include the absence of tumor-specific antigens, downregulation of antigen presentation molecules and suppression of T cell infiltration. Emerging evidence has indicated that bone and liver metastases might induce primary resistance to immunotherapy by regulating the immune microenvironment (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on cancer therapy, the use of anti-PD-1 and anti-PD-L1 mAbs has been seen as a significant milestone in managing cancer. This suggests that the inhibition of PD-1 and PDL-1 can be a highly effective strategy to reduce T-cell exhaustion, which, in turn, contains or manages various infectious diseases ( Figure 3 ) [ 149 , 166 ]. It is very well stated by Mohammed et al (2022) that the restoration of worn-out or exhausted T cells may be a successful tactic to combat COVID-19 [ 149 ].…”
Section: Immunomodulatory Approaches To Overcome T-cell Exhaustionmentioning
confidence: 99%